Are granites and granulites consanguineous? - Korhonen, F.; Brown, M.; Clark, Christopher; Foden, J.; Taylor, R. (GEOLOGICAL SOC AMER, INC, 2015)
© 2015 Geological Society of America. An important question in petrology is whether the production of granite magma in orogens is a closed-system process with respect to mass input from the mantle. This is commonly addressed by inversion of geochemical data from upper crustal granites, but a complementary approach is to assess the kinship of residual granulites and associated granites in exhumed orogenic crust. Here we report geochemical data for a suite of contemporaneous metasedimentary granulites and granites from the Eastern Ghats Province, India, part of a Grenville-age orogen. The prograde metamorphic evolution involved increasing temperature (T) and pressure (P) to a metamorphic peak at >1000 °C at ~0.7 GPa, followed by slow close-to-isobaric cooling. Variations in the composition of granites are interpreted to be due to local processes, including fractionation during melting or crystallization, and/or peritectic mineral entrainment. The Nd and Sr isotope compositions of the granites can be matched by mixing between different granulites, suggesting that they may have been derived solely from sedimentary protoliths leaving behind granulite facies residues. However, by including geochemical data from an adjacent area to the north, it becomes clear that an increasingly important mass input from the mantle was involved in granite genesis from southwest to northeast in the Eastern Ghats Province, as confirmed by modeling assimilation-fractional crystallization between an exemplar mantle-derived melt at 1000 Ma and the residual granulites. The extreme peak metamorphic temperature and P-T evolution suggest extended lithosphere that relaxed thermally to its former thickness during slow cooling. We postulate that the spatial variation in mantle input to the granites was related to changing feedback between the rates of extension and flux of mantle melt.